Butterflies (Lepidoptera: Nymphalidae) associated with pig carrions in Malaysia - Heo, Chong Chin; Marwi, Mohamed Abdullah; Abdullah, Wan Omar; Jeffery, John; Azirun, Mohd Sofian; Chen, Chee Dhang; Ishak, Ismarulyusda; Omar, Baharudin (Universiti Kebangsaan Malaysia Press, 2010)
An entomological study was conducted in Tanjung Sepat, Selangor, Malaysia in May until September 2007 revealing five species of butterflies (all from family Nymphalidae) were attracted to pig carcasses placed in an oil palm plantation. Euploea mulciber (Cramer 1777), Hypolimnas bolina (Linnaeus 1758), Elymnias hypermnestra (Linnaeus 1763), Mycalesis mineus (Linnaeus 1758) and Ypthima baldus (Fabricius 1775) came to the carcasses at different stages of decomposition. From this study, we know that nymphalid butterflies are attracted to carcasses but their roles are most probably unimportant in post-mortem estimation.